Ebenezer Obey and the rhetoric of contradiction. Issue 2 (3rd April 2017) - Mosobalaje, Adebayo
Abstract: A dialectical relationship exists between popular music and society. While popular music is a product of society, it also in turn not only reflects but also refracts society – it upholds and upbraids society in terms of agency. This paper, therefore, examines selected lyrics from Ebenezer Obey's jùjú song poetry in the framework of society-art dialectic and the rhetoric of contradiction. To achieve the objective, a cultural perspective is used to analyse the depictions of women, religion and morality in the selected lyrics. The results show that there is a veritable relationship of influence between the artiste and the society. Ebenezer Obey is a contemporary agent of the oral chanter in his negotiation/occupation of the urban city space with his urban underclass and wealthy elite fans. He is also revealed through his music to be a site upon which the contradictory ideologies of his Yoruba worldview and the disjunctive rhetorical patterns of the artistic heritage of his people engage in a ceaseless play. We shall begin the paper by introducing the categories of the rhetoric of contradiction and thereafter examine the biography and song production of Ebenezer Obey in order to situate the social and the religious contexts of his music.